Resilient energy management incorporating energy storage system and network reconfiguration: A framework of cyber‐physical system. Issue 8 (8th April 2022) - Jalilpoor, Kamran; Ameli, Mohammad Taghi; Azad, Sasan; Sayadi, Zahra
Abstract: Due to increasing the intricacies of cyber‐physical systems (CPSs) and the severity of natural phenomena, upgrading network planning is vital to reduce the vulnerability of these systems. This study develops a novel preventive‐corrective resilient energy management strategy (PC‐REMS) for a CPS in two stages, exploiting the network reconfiguration (NR) and energy storage systems (ESSs) capacity. The first stage of the proposed PC‐REMS follows preventive actions based on contingency faults. In contrast, the second stage applies corrective measures for improving the CPS resilience to cope with natural physical disasters. Vulnerability assessment data is sent to the physical power system daily through the communication network. The first stage of preparing the CPS for predictable faults focuses on pre‐scheduled ESSs and preventive NR to minimise the expected energy curtailment cost. The second stage involves the network recovery in real‐time through corrective NR to minimise energy curtailment cost after the faults. Three resistance, recovery, and resilience indices are introduced for evaluating the effectiveness of the model. The proposed model is examined by performing multiple simulations on the 33 and 118‐bus radial test systems. The simulation results show the efficiency of the proposed PC‐REMS model in dealing with predictable disasters to improve the CPS resilience.